Religious Moderation, Tolerance Moderasi Beragama di Desa Ngandagan Kecamatan Pituruh Kabupaten Purworejo Provinsi Jawa Tengah - Mulyani, Wiwik (Lembaga Penelitian dan Pengabdian Kepada Masyarakat of Institut Agama Islam Negeri Metro, 2023)
This study aims to describe the uniqueness that exists in Ngandagan Village, Pituruh District, Purworejo Regency, Central Java. It started with the researcher’s interest in this area, where the community adheres to various religions but has religious moderation. Harmony and peace is always well maintained. In interviews with village officials, community leaders in Ngandagan village as well as several members of the Ngandagan village community, is was found that this village community adheres to various religions including Islam, Protestant Christianity, adn Catholic Christianity. Because of this diversity and the social harmony that accompanies it, further research is needed on the things behind this event. The methodology used is the method of observation and interviews where to get the data, the authors conduct observations and structured or planned interviews. The findings in this paper include. First, the community has long adhered to religious differences, even since the G30S PKI era, so that differences are very natural in that society. Furthermore, because of family ties. Where in one family member adheres to various religions as well because it has become a tardition to respect fellow religious people.